Glioblastoma Multiforme with Long Term Survival - Zaki, Adeeba; Nida-e-Zehra; Rashid, Yasmin Abdul; Jabbar, Adnan Abdul (Archives of Clinical and Medical Case Reports, 2022)
Background: GBM is the most common and aggressive primary malignant brain tumor. Despite multimodality approach in the treatment of brain tumor, survival of the patients with GBM remains poor. The median survival of glioblastoma patients is 12 months. However, 35% of the patients survives for more than 3 years and are referred to as long-term survivors. When disease progression occurs 6-month progression-free survival (PFS) is usually lower than 15%. Case Presentation: A 68-years-old gentleman presented with a space occupying lesion in right frontoparietal region in March 2011, work up showed space (solid enhancing 4.3 x 4.2 x 2.7 cm & cystic component 3.6 x 3.5 x 3 cm). He underwent craniotomy for excision of the lesion, Postoperaticve scan confirmed gross total resection. Histopathology revealed Glioblastoma Multiforme. He received concomitant chemoradiation (60 Gy/30 Fr) with Temozolomide 75mg/m2 followed by monthly temozolomide (day 1-5 q 28 day cycle)., He was continued on monthly temozolomide (from July 2011- July 2015) with imaging Q 3 montly which revealed no residual disease. Patient primary oncologist was changed and since there was no residual disease and no evidence of prolong use of TMZ, it was stopped and was put on surveillance. He remained in remission till September 2017, when he developed recurrent disease. . He underwent right redo craniotomy & excision of SOL in November 2017. Histopathology revealed GBM. He was started on monthly temozolomide q 28day cycle from December 2017 till February 2018, interim scans in Feb shows disease progression he then received Bevacizumab and irrinotecan Q3weekly till April 2018 interim scans shows disease progression at his time his clinical condition also deteriorated and was not a candidate for any further systemic treatment hence advised palliative care and patient expired in May 2018. This is a rare cas